The establishment of in vitro human induced pluripotent stem cell-derived neurons - Izyan Mohd Idris,; Nur Jannaim Muhamad,; Julaina Abdul Jalil,; Fatimah Diana Amin Nordin,; Rosnani Mohamed,; Adiratna Mat Ripen,; Gee, Jun Tye; Wan Safwani Wan Kamarul Zaman,; Muhammad Dain Yazid,; Min, Hwei Ng (Universiti Kebangsaan Malaysia, 2023)
Induced pluripotent stem cells (iPSCs) have been generated using different reprogramming strategies. Lentiviruses remain a strategic method for cell reprogramming as it is highly efficient in gene transfer. The latest fourth-generation lentiviral packaging systems claimed to be efficient and safe. However, modifications made to enhance safety of lentiviral vectors have been shown to affect vector performance. In this study, we established that the fourth-generation lentiviral packaging system can produce high-titre lentiviruses with high-transduction efficiencies. Subsequently, the robustness and reproducibility of generating iPSCs from adult human dermal fibroblasts were tested using these lentiviruses. The use of fourth-generation lentiviruses consistently generates iPSCs with similar efficiency and quality in different primary cell lines. This study demonstrated that the human-derived iPSCs can be maintained using mitomycin-C inactivated feeder cells. The iPSCs clones highly expressed key pluripotency markers and can spontaneously differentiate into cells from the three embryonic germ layers. The iPSCs generated were able to differentiate into neural stem cell lineages, producing cells expressing Nestin and Sox2 as well as able to further differentiate into neurons with more than 70% efficiency. The data demonstrated that the use of the fourth-generation lentiviral packaging to produce lentiviruses for iPSCs generation is robust and reproducible as it can generate iPSCs from different adult dermal fibroblasts with the potential to differentiate into neural stem cells and neurons. The use of safer lentiviral packaging systems combined with established vector plasmids will help to expedite the generation of iPSCs for clinical applications.